Green extraction methods for isolation of bioactive substances from coffee seed and spent - Mediani, Ahmed; Kamal, Nurkhalida; Soo, Yee Lee; Abas, Faridah; Farag, Mohamed A. (Taylor & Francis, 2023)
Coffee is recognized worldwide as a top beverage owing to its several associated health benefits mediated by a complex mixture of unique bioactive substances. Chlorogenic acids are the key components of the phenolic fraction in green coffee seeds, accounting for up to 14% of the dry matter. The manufacturing of decaffeinated coffee demands efficient caffeine extraction from seeds and spent without solvent history effect for safety considerations. This has prompted researchers to investigate eco-friendly and cost-effective extraction technologies. Current extraction processes are not environmentally sustainable and have harmful consequences on humans. To date, developing a single standard method for effective extraction of certain complex compounds from coffee seeds remained a challenging procedure. The current review aims to give updated technical information regarding coffee plant green extraction methods, their advantages and disadvantages, and factors affecting efficacies for the recovery of bioactive compounds in coffee seeds and coffee spent. A comparative review of the uses of innovative green extraction techniques for coffee bioactive substances is introduced to present alternatives to conventional extraction methods. The most interesting finding was that the maximum total extractions of catechin (50.6 g/100 g) and caffeine (46.2 g/100 g) were achieved with enzymes in pressurized liquid extraction (PLE), and PLE-assisted with enzymes exhibited an enhancement in total phenolics and overall antioxidant compared to 50% hydro-ethanolic solutions. In addition, it has been claimed that the ultrasonic extraction can cut extraction time by 37% and temperature by 13%. These green extraction techniques represent favorable approaches to the exploitation of coffee chemicals as bioactives to explore their wide-reaching applications at an industrial level and for their valorization.